The mediating role of parent-child conflict in the relationship between self-differentiation and social anxiety - Mahbobeh , Bakhshaei; Azadi , Mehran (Applied Family Therapy Journal (AFTJ), 2020)
Aim: This study aimed to investigate the mediating role of parent-child conflict in the relationship between self-differentiation and social anxiety. Method: This is a descriptive correlational study. This study’s statistical population was female high school students who study in the 2nd district of Tehran in the academic year of 2018-19. Sampling was performed by random multi-stage clustering. First, three high schools were selected from the girls’ high schools in District 2 of Tehran. Then, two classes were selected from each high school according to their educational levels. A sample of 287 students was selected by random cluster sampling, and they answered the Differentiation Questionnaire (Scorn, 1998), Parent-Child Conflict Tactics (‎Straus, 1990), and Social Anxiety Questionnaire (Liebowitz, 1999). Results: The results of the correlation coefficient showed that there was a significant correlation between the total score of differentiation (r = -0.201) as well as subscales of my position (r = -0.256), emotional escape (r = -0.203), and fusion with others (r = -0.180) with social anxiety at the level of 0.01. Also, there was a significant correlation between the subscale of emotional responsiveness (r =-0.156) and social anxiety at the level of 0.05. There was also a correlation between parent-child conflict and social anxiety (r = 0.188) and between verbal aggression subscale (r = 0.186) and physical aggression subscale (r = 0.179) with social anxiety. Besides, the path coefficient model results showed a significant direct relationship between differentiation and social anxiety and between parent-child conflict and social anxiety (p = 0.01). Still, there was no significant direct effect between differentiation and parent-child conflict (p<0.05). Conclusion: The results showed that the consequence of mothers’ differentiation is to reduce the conflict between parents and children and reduce anxiety in children and adolescents because differentiated individuals differentiate between emotional and intellectual processes and are not influenced by others’ thoughts and behavior.